Factors influencing incomplete fusion in automatic girth welding of oil and gas pipelines - Zhili LUO; Yongli SUI (You-qi chuyun)
In view of the incomplete fusion occurred in the automatic girth welding of oil and gas pipelines, the factors influencing the incomplete fusion were studied with the welding procedure test and numerical simulation in combination. The results show that the swing width of the welding torch gradually increases for welding within the range from 3:00 to 6:00 o'clock. During this process, the welding process has the welding current decreased and the welding speed slowed down if the heat input remains unchanged. In this case, a larger swing width is helpful to increase the welding pool depth on the groove wall, thus guaranteeing the stability of weld droplet transition and reducing the risk of incomplete fusion on the wall. Besides, the weld morphology at the position of 4:30-6:00 was very poor, and the "hump weld" in the current pass will increase the probability of incomplete fusion in the next pass. In addition, the welding temperature field is in a serrated shape during the swing welding, which can be effectively eliminated at the swing frequency of 5 times/s or above. The research results can provide reference for improving the quality and efficiency of pipeline automatic welding.